2017
DOI: 10.1155/2017/2936461
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Methicillin-ResistantStaphylococcus aureust11469 and a Poultry Endemic Strain t002 (ST5) Are Present in Chicken in Ebonyi State, Nigeria

Abstract: Background The changing epidemiology of methicillin-resistant Staphylococcus aureus (MRSA) from a hospital-associated pathogen to an organism commonly found in the community and in livestock reflects an organism well-equipped to survive in diverse environments and adjust to different environmental conditions including antimicrobial use. Methods We investigated the molecular epidemiology of S. aureus and MRSA in poultry in Ebonyi State, Nigeria. Samples were collected from 1800 birds on 9 different farms within… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 29 publications
1
19
1
Order By: Relevance
“…MRSA strains has been previously isolated from nasal swabs of workers in farms ( Macori et al, 2017 ). The poultry strains in this study were MRSA negative; however, Nworie et al (2017) has reported MRSA in poultry in Nigeria. Lack of lukS-PV/lukF-PV in Nigerian MRSA strains has been previously reported by Kolawole et al (2013) .…”
Section: Discussioncontrasting
confidence: 56%
“…MRSA strains has been previously isolated from nasal swabs of workers in farms ( Macori et al, 2017 ). The poultry strains in this study were MRSA negative; however, Nworie et al (2017) has reported MRSA in poultry in Nigeria. Lack of lukS-PV/lukF-PV in Nigerian MRSA strains has been previously reported by Kolawole et al (2013) .…”
Section: Discussioncontrasting
confidence: 56%
“…Earlier studies have reported the presence of S. aureus , including MRSA, in live bird and chicken carcasses at poultry markets in Zaria [ 20 ] and Maiduguri [ 9 ] in northern Nigeria. A high prevalence (80.0%) of S. aureus was reported in samples from live chicken among small holder farms in Zaria [ 21 ], while Nworie et al [ 8 ] reported a low MRSA prevalence (0.8%) in poultry farms in Ebonyi State, southeastern Nigeria.…”
Section: Discussionmentioning
confidence: 99%
“…Regrettably, there are few data about MRSA, its molecular properties and the transmission routes, especially via meat production and marketing chains from low-income countries, like Nigeria. Earlier studies under separate investigations have documented the detection of MRSA in samples of human [ 6 , 7 ] and animal origin [ 8 , 9 ]. Continuous surveillance using the latest technology will provide in-depth analysis of MRSA profiles for a better understanding of the origins and dissemination patterns in human and animal populations across different geographical locations.…”
Section: Introductionmentioning
confidence: 99%
“…It is a common and widespread human lineage that has found its way into poultry where it is frequently being encountered and from where it has spread to other livestock [53][54][55]. It was recently detected in swab samples collected from the nasal cavity of farm animals (cattle and goats) and abattoir workers where these animals as well as pigs are processed [23], and in poultry in Ebonyi State, Nigeria [21] as well as from pigs in Senegal [56]. It has also been reported in clinical isolates from humans in Nigeria [14,57].…”
Section: Source (N)mentioning
confidence: 99%
“…This testing may not be reliable, especially in Nigeria where biochemical reagents are often purchased from traders. However, only Nworie et al [21] in Ebonyi State, Southeast Nigeria and Ayeni et al [22] in Ogun State, in the Southwest used genotypic characterization techniques to detect S. aureus isolates from poultry while Odetokun et al [23] in the Southwest and, Momoh et al [24] as well as Otalu et al [25] in the Northcentral also reported the molecular epidemiology of S. aureus from food animals and occupationally-exposed humans in Nigeria. Molecular epidemiological data on S. aureus contaminating raw meat meant for human consumption and humans with occupational contact are limited in Nigeria.…”
Section: Introductionmentioning
confidence: 99%